Case studies in settlements of agrarian reform in Minas Gerais – Brazil (Research, Society and Development, 2022)
The characteristics and their homogeneous and heterogeneous aspects represent the central problem of this text, their objective is to describe the agrarian reality of the Betinho, Carlito Maia, Morro Grande, Santo Antônio II Settlements, in the state of Minas Gerais. The methodology used the integration of quantitative and qualitative approaches in the case study modality, using the techniques of data collection: direct observation and statistical indicators contained in the Project Database RADIS / UFMT. The analyzes were based on the research categories: Infrastructure / environmental management; economic / technological basis and social relations of production. Based on the cases analyzed, it is considered that the relationship between rural settlements and local development is part of a political field.